Learn Excel 2016 for OS X - Hart-Davis, Guy (Apress : Imprint: Apress, 2015)
Microsoft Excel 2016 for Mac OS X is a powerful application, but many of its most impressive features can be difficult to find. Learn Excel 2016 for OS X by Guy Hart-Davis is a practical, hands-on approach to learning all of the details of Excel 2016 in order to get work done efficiently on OS X. From using formulas and functions to creating databases, from analyzing data to automating tasks, you'll learn everything you need to know to put this powerful application to use for a variety of tasks.